Cardiomyopathies in children - Young Mi Hong (Korean Pediatric Society, 2013)
Cardiomyopathy (CMP) is a heterogeneous disease caused by a functional abnormality of the cardiac muscle. CMP is of 2 major types, dilated and hypertrophic, and is further classified as either primary or secondary. Secondary CMP is caused by extrinsic factors, including infection, ischemia, hypertension, and metabolic disorders. Primary CMP is diagnosed when the extrinsic factors of secondary CMP are absent. Furthermore, the World Health Organization, American Heart Association, and European Cardiology Association have different systems for clinically classifying primary CMP. Primary CMP is rare and associated with a family history of the disease, implying that genetic factors might affect its incidence. In addition, the incidence of CMP varies widely according to patient ethnicity. Genetic testing plays an important role in the care of patients with CMP and their families because it confirms diagnosis, determines the appropriate care for the patient, and possibly affects patient prognosis. The diagnosis and genetic identification of CMP in patients' families allow the possibility to identify novel genes that may lead to new treatments. This review focuses on the epidemiology, pathophysiology, diagnosis, and treatment of CMP, with the aim of providing pediatricians with insights that may be helpful in the early identification and management of idiopathic CMP in children.